2014
DOI: 10.3354/aei00090
|View full text |Cite
|
Sign up to set email alerts
|

Salmon lice infection on wild salmonids in marine protected areas: an evaluation of the Norwegian ‘National Salmon Fjords’

Abstract: In Norway, 29 fjords and 52 rivers have been designated for protection in order to prevent the infection of important populations of wild salmonids with salmon lice of farm origin. We evaluated the effect of this protection on the lice infection pressure for wild salmonids based on lice counts performed on wild-caught sea trout and Arctic charr inside onethird of these protected fjords (known as 'National Salmon Fjords'). Results indicate that these areas may provide a certain extent of protection against lice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 61 publications
7
114
0
Order By: Relevance
“…Schram et al (1998) observed the same temporal pattern in lice numbers on wild sea trout Salmo trutta in areas with no salmon farming. Additionally, there seems to be a spatial component in lice abundance on wild fish, suggesting lower lice numbers in the north (Altafjord) (Serra-Llinares et al 2014). A similar spatial pattern in lice abundance was observed in farmed fish (Jansen et al 2012).…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wisupporting
confidence: 51%
See 4 more Smart Citations
“…Schram et al (1998) observed the same temporal pattern in lice numbers on wild sea trout Salmo trutta in areas with no salmon farming. Additionally, there seems to be a spatial component in lice abundance on wild fish, suggesting lower lice numbers in the north (Altafjord) (Serra-Llinares et al 2014). A similar spatial pattern in lice abundance was observed in farmed fish (Jansen et al 2012).…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wisupporting
confidence: 51%
“…3 in Serra-Llinares et al 2014). Copepodite production in farms was estimated using the reproduction model of Stien et al (2005), with temperature as a determinant of the per capita reproductive rate per female louse.…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wimentioning
confidence: 99%
See 3 more Smart Citations